Cooperation Between Systemic IgG1 and Mucosal Dimeric IgA2 Monoclonal Anti-HIV Env Antibodies: Passive Immunization Protects Indian Rhesus Macaques Against Mucosal SHIV Challenges - Gong, Siqi; Lakhashe, Samir K.; Hariraju, Dinesh; Scinto, Hanna; Lanzavecchia, Antonio; Cameroni, Elisabetta; Corti, Davide; Ratcliffe, Sarah J.; Rogers, Kenneth A.; Xiao, Peng; Fontenot, Jane; Villinger, François; et al. (Frontiers in Immunology, 2021)
Understanding the interplay between systemic and mucosal anti-HIV antibodies can provide important insights to develop new prevention strategies. We used passive immunization via systemic and/or mucosal routes to establish cause-and-effect between well-characterized monoclonal antibodies and protection against intrarectal (i.r.) SHIV challenge. In a pilot study, for which we re-used animals previously exposed to SHIV but completely protected from viremia by different classes of anti-HIV neutralizing monoclonal antibodies (mAbs), we made a surprise finding: low-dose intravenous (i.v.) HGN194-IgG1, a human neutralizing mAb against the conserved V3-loop crown, was ineffective when given alone but protected 100% of animals when combined with i.r. applied HGN194-dIgA2 that by itself had only protected 17% of the animals. Here we sought to confirm the unexpected synergy between systemically administered IgG1 and mucosally applied dIgA HGN194 forms using six groups of naïve macaques (n=6/group). Animals received i.v. HGN194-IgG1 alone or combined with i.r.-administered dIgA forms; controls remained untreated. HGN194-IgG1 i.v. doses were given 24 hours before – and all i.r. dIgA doses 30 min before – i.r. exposure to a single high-dose of SHIV-1157ipEL-p. All controls became viremic. Among passively immunized animals, the combination of IgG1+dIgA2 again protected 100% of the animals. In contrast, single-agent i.v. IgG1 protected only one of six animals (17%) – consistent with our pilot data. IgG1 combined with dIgA1 or dIgA1+dIgA2 protected 83% (5/6) of the animals. The dIgA1+dIgA2 combination without the systemically administered dose of IgG1 protected 67% (4/6) of the macaques. We conclude that combining suboptimal antibody defenses at systemic and mucosal levels can yield synergy and completely prevent virus acquisition.